On wings with non-elliptic lift distributions - Bragado Aldana, Estela; Lone, Mudassir; Riaz, Atif (International Council of the Aeronautical Sciences (ICAS), 2021)
Non-elliptic lift distributions were originally conceived by Prandtl as a solution for wings having optimal aerodynamic and structural efficiency. Since 1933, many researchers have expanded on this theory to confirm that it explicitly facilitates the trade-off between induced drag and weight, and have unveiled other potential benefits such as proverse yaw. This theory is seen as a promising alternative to redefine the underlying principles of conceptual wing design in the search for a step increase in efficiency. Given the recent revival of this approach, in this paper the authors present a concise review of its theoretical basis, the developments carried out in this area and their relevance to the future of aviation.
© The Author.
Keywords: Non-elliptic lift distributions; wing design; aero-structural efficiency; induced drag; proverse yaw